Education Transformation: Curriculum Management to Improve Learning Quality in RA Rahmatullah - Indri Nuraeni; Nisrina Nur Khaliza; Yesi Akmal Nurjanah; Risbon Sianturi (Universitas Muhammadiyah Enrekang, 2023)
This research aims to determine the management of the curriculum at RA Rahmatullah to improve the quality of learning. Curriculum management is related to managing learning experiences that require strategies and that can produce learning productivity for children. The type of research used in this research is qualitative research, namely research carried out by collecting data using interview methods and documentation studies at RA Rahmatullah which is carried out to provide study material for both students and the school. Education management at RA Rahmatullah has been arranged systematically, each teacher has their own task to manage the educational component. Curriculum management is managed well under the auspices of the Tasikmalaya Ministry of Religion. Core Competencies (KI) in the 2013 Early Childhood Education Curriculum is the level of ability to achieve STTPA that PAUD students must have at the age of 6, which includes spiritual attitudes, social attitudes, knowledge and skills. Thus, there are many learning plans for the 2013 curriculum at RA Rahmatullah, namely: 1) annual program (prota), 2) semester program (premes), 3) weekly learning implementation plan (RPPM), 4) daily program plan (RPPH), 5 ) evaluation carried out at RA Rahmatullah uses authentic evaluation.